Using a narrative approach in self-help groups for young people experiencing employment problems: Japanese experience - D. N. Iashin (Вестник университета, 2025)
This article examines the problem of marginalisation of young people in the post-industrial society of Japan who experience the mental state of ikizurasa, consisting of feelings of disunity, isolation, anxiety, and leading to the inability to obtain a stable and well-paid job. The socio-economic conditions for the emergence and spread of this condition among Japanese youth are described. Its socio-economic and personal-mental aspects are highlighted and disclosed. It has been established that the mental state similar to the ikizurasa is not a specifically Japanese phenomenon, as it is observed in the countries with a Western mentality, in particular in Europe. A critical analysis of the socio-political assistance programmes proposed by the Japanese government is conducted, revealing their weak effectiveness when applied to subjects experiencing the ikizurasa. A narrative approach has been proposed as an alternative to the government employment programmes. The characteristics of psychological assistance formats that use narrative methods are given. Using the example of the social practice of self-help groups, the psychotherapeutic effectiveness of the narrative approach has been identified and substantiated,consisting in the individual’s awareness of their own needs, strengthening the feelings of stability and integration of their Self, and in the emergence of an active subject position in relation to their own employment. Prospects for further research are outlined.